2006
DOI: 10.1071/ah060322
|View full text |Cite
|
Sign up to set email alerts
|

"There's no point in complaining, nothing changes": rural disaffection with complaints as an improvement method

Abstract: Rural consumers' disaffection with health complaints as a means to quality improvement poses a significant barrier to consumer engagement in quality assurance processes. Provider practices may need to change to regain community confidence in quality improvement processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The reduced likelihood of patients with limited English complaining has been supported in recent studies about complaints 13 14. Under-representation in complaints does not necessarily signify satisfaction with services; rather, it may indicate poor access, cynicism about complaining or poor knowledge about complaints procedures 15. When patients with limited English are actively asked to comment on services, they may then complain at a higher rate 16…”
Section: Discussionmentioning
confidence: 94%
“…The reduced likelihood of patients with limited English complaining has been supported in recent studies about complaints 13 14. Under-representation in complaints does not necessarily signify satisfaction with services; rather, it may indicate poor access, cynicism about complaining or poor knowledge about complaints procedures 15. When patients with limited English are actively asked to comment on services, they may then complain at a higher rate 16…”
Section: Discussionmentioning
confidence: 94%
“…A retrospective analysis of complaints to the Victoria's Health Services Commissioner showed that rural consumers were underrepresented compared to their urban counterparts (Smith et al, 2006), which may be due to a reduced opportunity to access health services in rural areas owing to workforce shortages (Jones et al, 2005). Surveys indicate that Victoria's rural consumers (in Australia) are less likely than those in metropolitan areas to make formal complaints to the Health Services Commissioner and that access to health services is the most important issue amongst this cohort (Jones et al, 2006). Consumers in larger rural towns appear to be more willing to complain to hospital boards or health complaints commissions than those in small towns, who reported they would instead complain to the local provider (Humphreys et al, 2005).…”
Section: Complaint Patterns and Correlatesmentioning
confidence: 99%
“…This may partly explain the higher rates of head injuries and TBI observed in remote parts of Australia. In much of remote Australia, relatively small populations are spread across large areas, presenting practical challenges for injury prevention [27,28]. The risk of some injuries, as well as the ability to retrieve injured youth and young adults to acute care services in a timely manner, may be impeded by distance and remoteness.…”
Section: Discussionmentioning
confidence: 99%